Consumer privacy in the era of big data: A survey of smartphone users' concerns - Yapraklı, Tevfik Şükrü; Ünalan, Musa (My University, 2017)
Smartphones increase rapidly and become high-speed mobile data networks progressively appearing everywhere in the recent years. Also, there is a large and ever increasing number of mobile phone applications on the market. In this case, consumer privacy become critically important because sellers might access a large volume of personal information. This paper attempts to identify the consumer privacy and concerns in the context of big data and to explore how consumers’ demographic differences may affect their concerns for information privacy. The smartphone owners’ demographic differences and their concerns over privacy are analyzed, based on a survey of 392 smartphone users in Erzurum. It has been found that consumers’ demographic differences have varying degrees of impact on their concerns for information privacy in the context of big data.
Bildiri - Yayımlanmış
Keywords: Big data; Consumer privacy; Privacy concerns; Smartphone users